Blunt renal vascular trauma resulting in arterial avulsion injury with a nephron‐sparing outcome. Issue 6 (7th June 2019) - Clements, Warren; Moriarty, Heather K
Summary: Blunt renal vascular traumatic injury is uncommon, and most injuries can be managed conservatively in a patient who is clinically stable. Pseudoaneurysm or active bleeding at presentation is rare and in an unstable patient, endovascular techniques offer a low morbidity option for rapid treatment. We present an unusual case of avulsion of a second order renal artery from the main renal artery, with active bleeding at presentation treated by excluding the bleed with a stent graft. This was complicated by delayed pseudoaneurysm formation, treated with a larger stent graft. This resulted in preservation of renal parenchyma and renal function in a young patient.